(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes the methodological tasks of pedagogical social partnership in preparing students for intellectual activity. It highlights the theoretical and practical aspects of cooperation between higher education institutions, the industrial sector, and social organizations. Special emphasis is placed on the methodological significance of cooperative learning environments, reflection, innovative tasks, and practical integration in fostering students’ intellectual capacity.